PCBN composite sheet and sintering process thereof
By performing the thermal prepression sintering process and the six-sided top pressure sintering process in the discharge plasma furnace chamber, the problems of uneven surfaces and insufficient hardness of the traditional PCBN composite sheet are solved, and high hardness and high flatness PCBN composite sheets are achieved. Meets the needs of precision cutting processing.
Patent Information
- Application Number
- CN202411549079.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-02-07
AI Technical Summary
During the sintering process, the PCBN composite sheets are uneven and the thickness is uneven due to the deformation of the cemented carbide backing, which makes it difficult to meet the needs of precision cutting processing. At the same time, the PCBN prepared by the existing discharge plasma rapid sintering method is relatively low, making it difficult to Meet precision machining requirements.
The thermal prepression sintering process is adopted in the discharge plasma furnace chamber to ensure that the cemented carbide backing is uniformly subjected to high temperature and high pressure, and further heat and pressurize through the hexagonal top pressure sintering process to ensure the density of the PCBN layer and Surface flatness.
It achieves the effects of high surface flatness, high hardness and large cutting volume of PCBN composite sheets, meeting the needs of precision cutting processing.
Smart Images

Figure CN119390456A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of superhard materials, and in particular to a PCBN composite sheet and a sintering process thereof. Background Art
[0002] Polycrystalline cubic boron nitride (PCBN) composite sheet is made of CBN powder, binder and cemented carbide substrate sintered under high temperature and high pressure conditions. It combines the high wear resistance of superhard materials and the high impact resistance of cemented carbide. It is mainly used in metal surface treatment and precision cutting.
[0003] Traditional PCBN composite sheets are generally made by a six-sided top press. The six-sided top press is composed of six relatively moving hydraulic plungers driving carbide pressure heads. The raw material powder is loaded into a container, and a pyrophyllite block as a pressure medium is set outside. It is placed between the top hammers of the ultra-high pressure equipment and made under high pressure (≥4GPa) and high temperature (≥1300℃). PCBN composite sheets made by a six-sided top press generally have strong hardness, but the PCBN layer bonded to the surface of the carbide substrate in the PCBN composite sheet has problems of uneven surface and uneven thickness, making it difficult to meet the requirements of precision cutting.
[0004] In the prior art, PCBN is also prepared by spark plasma rapid sintering. Its main feature is that charges are accumulated between the surfaces of raw material powder particles through pulse discharge. After accumulation to a certain extent, instantaneous plasma discharge occurs, and the temperature at the discharge point rises rapidly, causing sintering between particles. This method keeps the PCBN crystal structure in the finished product unchanged. However, the hardness of PCBN prepared by spark plasma rapid sintering is relatively low, and it is difficult to meet the requirements of cutting quality, cutting efficiency and cutting life in precision machining. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides a PCBN composite sheet sintering process. The PCBN composite sheet produced by the sintering process has high surface flatness, high hardness and high cutting amount.
[0006] The technical solution of the present invention is:
[0007] A PCBN composite sheet sintering process, characterized in that it comprises the following steps:
[0008] S1. Mixing: The CBN powder and the binder powder are mixed evenly according to a ratio and loaded into a graphite mold, wherein the graphite mold is provided with a cemented carbide backing;
[0009] S2. Hot pre-pressing and sintering: The graphite mold after filling is placed in a vacuum environment, and pre-heated and pressed at a pressure of 30-80Mpa and a temperature of 800-1200°C for sintering;
[0010] S3. Hot pre-pressing cooling: Cooling to below 80°C with the furnace to obtain a rough product;
[0011] S4. Six-sided top press sintering: The blank product after hot pre-pressing and cooling in S3 is placed in the cavity of a six-sided top press, heated from room temperature to 1400-1700°C, sintered under a pressure of 7-9Gpa, and kept warm for 20-30min;
[0012] S5. Cool to room temperature.
[0013] Furthermore, in the hot pre-pressing sintering, the graphite mold is placed in a spark plasma sintering furnace cavity, evacuated to below 5 Pa, heated from room temperature to 800-1200° C. at a heating rate of 60-100° C. / min, sintered under a pressure of 30-80 MPa, and kept warm for 5-10 minutes.
[0014] Furthermore, in the hot pre-pressing cooling in S3, the temperature in the furnace is above 1000°C and the temperature is lowered under power and pressure, the pressure is 20-60Mpa, and the cooling rate is 50-70°C / min; the temperature in the furnace is below 1000°C and the furnace is cooled to below 80°C.
[0015] Furthermore, the S1 comprises 30-85% CBN powder and 15-70% binder powder by mass percentage.
[0016] Furthermore, it comprises 50% CBN powder and 50% binder powder by mass percentage.
[0017] Furthermore, the particle size of the CBN powder is 1-2 μm.
[0018] Furthermore, the binder powder includes at least one of TiCN, TiC, and TiN, and the average particle size of the binder powder is 1-1.5 μm.
[0019] Furthermore, the cemented carbide backing is tungsten carbide-cobalt cemented carbide.
[0020] The present invention also provides a PCBN composite sheet, which is produced by any of the above-mentioned PCBN composite sheet sintering processes.
[0021] Furthermore, the thickness of the PCBN layer in the PCBN composite sheet is 0.4-0.75 mm.
[0022] The beneficial technical effects of the present invention are:
[0023] When the traditional six-sided top press sintering process is used to prepare PCBN composite sheets, a cemented carbide backing is placed in the mold, and then CBN powder and binder powder are evenly laid on the cemented carbide backing. Due to the strength of cemented carbide itself, the six-sided top press generates pressure on the six sides of the mold during high temperature and high pressure sintering, which will cause the cemented carbide backing layer to bulge and deform, resulting in an uneven PCBN layer on the cemented carbide backing and uneven thickness formed by sintering, which results in poor surface flatness of the PCBN composite sheet, affecting its performance.
[0024] Therefore, the present invention performs a preheating and pressing sintering process in a discharge plasma furnace chamber before the six-sided top pressure sintering process. On the one hand, during the preheating and pressing sintering, the discharge plasma simultaneously applies pressure to the upper and lower directions relative to the cemented carbide backing, and the cemented carbide will not be deformed up and down, but will be flattened a little, thereby fundamentally ensuring that the PCBN layer can be uniformly stressed during the hot pressing sintering process, so that the thickness formed by sintering is uniform, that is, the PCBN composite sheet has a good surface flatness; on the other hand, during the preheating and pressing sintering process in the discharge plasma furnace, charges accumulate between the surfaces of the CBN micropowder and the binder micropowder particles, and after accumulating to a certain extent, instantaneous plasma discharge occurs, and the temperature at the discharge point rises rapidly, so that the particles are sintered to form a PCBN layer. At the same time, the PCBN layer is compacted on the cemented carbide backing by the pressure applied up and down, thereby avoiding being squeezed and deformed in the subsequent six-sided top pressure sintering process, which affects its surface flatness.
[0025] The subsequent six-sided top pressure sintering process of the present invention further increases the temperature and pressure, so that the Co element in the cemented carbide backing can penetrate into the PCBN layer as a connector to fill the pores, making the PCBN layer more compact, and finally making it have better surface flatness while having higher hardness, wear resistance and corrosion resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a test diagram of the surface flatness of four PCBN composite sheets A1 in Example 1 of the present invention;
[0027] Figure 2 This is a test diagram of the surface flatness of four PCBN composite sheets B1 in Comparative Example 1 of the present invention;
[0028] Figure 3 This is a test diagram of the surface flatness of four PCBN composite sheets B2 in Comparative Example 2 of the present invention;
[0029] Figure 4 This is a test diagram of the surface flatness of four PCBN composite sheets B3 in Comparative Example 3 of the present invention. DETAILED DESCRIPTION
[0030] In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the specific implementation methods of the present invention are further described in detail below in conjunction with the drawings and examples. The following examples are used to illustrate the present invention but are not used to limit the scope of the present invention.
[0031] Example 1
[0032] A PCBN composite sheet sintering process comprises the following steps:
[0033] S1. Mixing: After the CBN powder and the binder powder are mixed evenly according to the ratio, they are loaded into a graphite mold, and the bottom surface of the graphite mold is provided with a cemented carbide backing;
[0034] Among them, by mass percentage, CBN micropowder is 50%, and the particle size of CBN micropowder is 2μm; binder micropowder is 50%, and the binder micropowder is composed of TiCN, TiC and TiN, and the mass percentage is TiCN:TiC:TiN=1:1:1, the average particle size of TiCN, TiC and TiN is 1.5μm, and the cemented carbide backing is tungsten carbide-cobalt cemented carbide.
[0035] S2. Hot pre-pressing sintering: Place the filled graphite mold in the cavity of the spark plasma sintering furnace, evacuate to below 5 Pa, heat from room temperature to 1200°C at a heating rate of 60°C / min, sinter under a pressure of 50MPa, and keep warm for 10 minutes.
[0036] S3. Hot pre-pressing cooling: when the temperature in the spark plasma sintering furnace cavity is above 1000°C, it is cooled with electricity and pressure, the cooling rate is 70°C / min, and the pressure is 60MPa; when the temperature in the furnace is below 1000°C, it is cooled to below 80°C at a pressure of 20MPa to obtain a rough product.
[0037] S4. Place the blank product after hot pre-pressing and cooling in S3 in the cavity of a six-sided top press, heat it from room temperature to 1500°C, sinter it under a pressure of 8 Gpa, and keep it warm for 20 minutes.
[0038] S5. After sintering, the furnace is cooled to room temperature, and the pressure is released and the mold is removed to obtain the PCBN composite sheet A1.
[0039] Comparative Example 1
[0040] A PCBN composite sheet sintering process comprises the following steps:
[0041] a1. Mixing: The mixing steps are the same as those in the above embodiment 1 and will not be repeated here.
[0042] a2. Spark plasma sintering: Place the filled graphite mold in the spark plasma sintering furnace cavity, evacuate to below 5Pa, heat from room temperature to 1500℃ at a heating rate of 80℃ / min, sinter at a pressure of 50Mpa, and keep warm for 30min.
[0043] a3. Cooling: After sintering, the temperature is above 1000°C and the temperature is cooled with electricity and pressure, the cooling rate is 70°C / min, and the pressure is 40MPa. The temperature in the furnace is below 1000°C and the furnace is cooled to below 80°C at a pressure of 15MPa. The pressure is released and the mold is demolded to obtain the PCBN composite sheet B1.
[0044] Comparative Example 2
[0045] A PCBN composite sheet sintering process comprises the following steps:
[0046] b1. Mixing: The mixing steps are the same as those in the above embodiment 1 and will not be repeated here.
[0047] b2. Six-sided top press sintering: Place the filled graphite mold in the cavity of the six-sided top press, heat it from room temperature to 1500°C, sinter it under a pressure of 8Gpa, and keep it warm for 30 minutes.
[0048] b3. Cooling. After sintering, the graphite mold is cooled along with the furnace, and the PCBN composite sheet B2 is obtained by pressure relief and demoulding.
[0049] Comparative Example 3
[0050] A PCBN composite sheet sintering process comprises the following steps:
[0051] c1. Mixing: Same as the mixing steps in Example 1 above.
[0052] c2. Pre-pressing: Place the filled graphite mold in an isostatic pressing device for pre-pressing, with a pre-pressing pressure of 10 MPa and a holding time of 5 minutes.
[0053] c3. Six-sided top pressure sintering: same as step b2 in the above comparative example 2.
[0054] c4. Cooling. After sintering, the graphite mold is cooled along with the furnace, and the PCBN composite sheet B3 is obtained by depressurizing and demoulding.
[0055] PCBN composite sheet surface flatness test
[0056] The surface flatness test is conducted using an ultrasonic flaw detector (1SET), and the thickness range of the PCBN layer bonded to the carbide backing in the PCBN composite sheet represents the surface flatness value of the PCBN composite sheet. The surface flatness of the PCBN composite sheet is an important quality indicator, which directly affects the cutting performance and life of the PCBN composite sheet. After using PCBN with uneven thickness to make a tool, the surface flatness of the processed product cannot meet the use requirements. At the same time, the PCBN thickness on the surface of the PCBN composite sheet is uneven. When it is used, the thin part is ground and the thicker part can no longer be used, which reduces the service life of the tool.
[0057] Therefore, to ensure the production and use of PCBN composite cutter products, the thickness of the PCBN layer is controlled within the range of 0.4-0.75mm, indicating that the surface flatness of the PCBN composite sheet is qualified. The different colors in the ultrasonic flaw detection results correspond to different thicknesses of the PCBN layer. To ensure the reliability of the test results, 4 PCBN composite sheets A1-B3 are prepared, and the surface flatness test results are taken from the minimum to maximum values of the corresponding four test samples.
[0058] Hardness test of PCBN composite sheet
[0059] The hardness test of PCBN composite sheet A1-B3 was carried out using a Knoop hardness tester (FALCON 500), wherein the Knoop indenter was tested under an indenter load of 5KG (HK5), and the PCBN layer of the PCBN composite sheet was the test layer.
[0060] Cutting volume test of PCBN composite inserts
[0061] Test equipment: Taichung Precision Machinery Vturn-20 CNC machine tool;
[0062] Test parameters: cutting depth ap = 0.1 mm, feed rate f = 0.1 mm, linear speed v = 200 m / s;
[0063] Processing workpiece: GrWMn, workpiece hardness HRC: 59-60, specification: φ95-100mm×120mm;
[0064] Test method: The products of Example 1 and Comparative Examples 1-3 were tested alternately, and the turning amount △V each time was 20000mm 3 The PCBN layer of each PCBN composite sheet is the blade surface. Check the wear status of the PCBN composite sheet blade until the blade breaks and record the data.
[0065] The test results of each test item of PCBN composite sheets A1-B3 are shown in Table 1.
[0066] Table 1
[0067]
[0068] From the test results in Table 1, it can be seen that the thickness of the PCBN layer of PCBN composite sheet A1 is 0.45-0.65mm, its surface flatness is standard, its hardness is 26.0±1.5Gpa, and the cutting volume reaches 144105mm 3 . And from Figure 1 It can be seen from the test diagram of the four samples of PCBN composite blade A1 that the thickness range of the PCBN layer of the four samples A1-(1) to A1-(4) of the PCBN composite sheet A1 is similar, which further illustrates that the sintering process of the present invention has high stability and can meet the production requirements of mass production of PCBN composite sheets with qualified surface flatness and high hardness.
[0069] The thickness of the PCBN layer of the PCBN composite sheet B1 is 0.40-0.70 mm, and its surface flatness is acceptable, but its hardness value is only 3.2±1.5 Gpa, which does not meet the use requirements, resulting in the inability to perform cutting volume testing.
[0070] When the spark plasma sintering process is used to prepare PCBN composite sheets, the use of pulse current to generate plasma and the pressurization during the sintering process are beneficial to reduce the sintering temperature of the powder. At the same time, the characteristics of low voltage and high current can make the powder sinter quickly and densely. It has the advantages of rapid temperature rise, short sintering time, and controllable component structure. However, compared with the six-sided top pressure sintering process, the sintering process cannot effectively make the Co element in the cemented carbide backing penetrate into the pores of the PCBN layer during the liquid phase sintering stage, resulting in poor density of the PCBN layer, which ultimately leads to poor hardness and wear resistance.
[0071] The hardness value of PCBN composite sheet B2 is 25.3±1.5Gpa, which is not much different from the hardness value of PCBN composite blade A1; however, the thickness of its PCBN layer is 0.35-(>0.80)mm, where >0.80mm means that the thickest part of the PCBN layer exceeds 0.8mm, that is, the surface of the composite sheet is extremely uneven, resulting in a cutting value of 109822mm 3 , which is much smaller than the cutting amount of PCBN composite insert A1. Figure 3It can be seen from the test diagram of the four samples of PCBN composite sheet B2 that the PCBN layer thickness range of the four samples B2-(1) to B2-(4) of the PCBN composite sheet B1 is extremely unevenly distributed, among which the PCBN layer thickness of B2-(1) is 0.40-0.75mm; the PCBN layer thickness of B2-(2) is (<0.30)-(>0.80)mm, among which <0.30mm means that the thinnest thickness of the PCBN layer does not reach 0.3mm, and >0.80mm means that the thickest part of the PCBN layer exceeds 0.8mm; the PCBN layer thickness of B2-(3) is 0.35-0.8mm, and the PCBN layer thickness of B2-(4) is 0.35-0.8mm, which further illustrates that the traditional six-sided top pressure sintering process cannot meet the production requirements of mass production of PCBN composite sheets with qualified surface flatness and high hardness.
[0072] The hardness value of PCBN composite sheet B3 is 24.6±1.5Gpa, which is not much different from the hardness value of low-content PCBN composite blade A1; however, the thickness of its PCBN layer is 0.35-(>0.80)mm, and the surface of the composite sheet is also extremely rough, resulting in its cutting amount value being much smaller than the cutting amount of PCBN composite sheet A1.
[0073] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. It should be pointed out that a person skilled in the art can make several improvements and modifications without departing from the technical principles of the present invention, and these improvements and modifications should also be regarded as within the scope of protection of the present invention.
Claims
1. A PCBN composite sheet sintering process, characterized in that: The following steps are involved: S1. Mixing: The CBN powder and the binder powder are mixed evenly according to a ratio and loaded into a graphite mold, wherein the graphite mold is provided with a cemented carbide backing; S2. Hot pre-pressing and sintering: The graphite mold after filling is placed in a vacuum environment, and pre-heated and pressed at a pressure of 30-80Mpa and a temperature of 800-1200°C for sintering; S3. Hot pre-pressing cooling: Cooling to below 80°C with the furnace to obtain a rough product; S4. Six-sided top press sintering: The blank product after hot pre-pressing and cooling in S3 is placed in the cavity of a six-sided top press, heated from room temperature to 1400-1700°C, sintered under a pressure of 7-9Gpa, and kept warm for 20-30min; S5. Cool to room temperature.
2. A PCBN composite sheet sintering process according to claim 1, characterized in that: In the hot pre-pressing sintering, the graphite mold is placed in a spark plasma sintering furnace cavity, evacuated to below 5 Pa, heated from room temperature to 800-1200° C. at a heating rate of 60-100° C. / min, sintered under a pressure of 30-80 MPa, and kept warm for 5-10 minutes.
3. A PCBN composite sheet sintering process according to claim 1, characterized in that: In the S3, the temperature in the furnace is above 1000°C and the temperature is lowered under power and pressure, the pressure is 20-60Mpa, and the cooling rate is 50-70°C / min; when the temperature in the furnace is below 1000°C, the temperature is cooled to below 80°C along with the furnace.
4. A PCBN composite sheet sintering process according to claim 1, characterized in that: The S1 comprises 30-85% CBN powder and 15-70% binder powder by mass percentage.
5. A PCBN composite sheet sintering process according to claim 4, characterized in that: The invention comprises 50% CBN micro powder and 50% binder micro powder by mass percentage.
6. A PCBN composite sheet sintering process according to claim 4, characterized in that: The particle size of the CBN powder is 1-2 μm.
7. A PCBN composite sheet sintering process according to claim 4, characterized in that: The binder powder includes at least one of TiCN, TiC and TiN, and the average particle size of the binder powder is 1-1.5 μm.
8. A PCBN composite sheet sintering process according to claim 1, characterized in that: The cemented carbide backing is tungsten carbide-cobalt cemented carbide.
9. A PCBN composite sheet, characterized in that: It is produced by the sintering process of a PCBN composite sheet as described in any one of claims 1-8.
10. The PCBN composite sheet according to claim 9, wherein the thickness of the PCBN layer in the PCBN composite sheet is 0.4-0.75 mm.
Citation Information
Patent Citations
Preparation method of polycrystal cubic boron nitride sintering body material
CN107098704A
Composite binding agent and preparation method thereof, and polycrystalline cubic boron nitride composite sheet and preparation method and application thereof
CN110370176A
Polycrystalline diamond compact and preparation method thereof
CN115555566A
Preparation method of polycrystalline diamond compact with high impact toughness
CN115582544A
Method for sintering polycrystal cubic boron nitride by plasma discharge
CN1817434A
Cited By
High-toughness polycrystalline cubic boron nitride composite sheet and preparation method thereof
CN120664883A
PCBN cutter composite material and sintering preparation process thereof
CN122406019A
PCBN cutting tool composite material and sintering preparation process thereof
CN122406019B